IV. STORAGE AND GERMINATION TESTS ON SHOREA JAVANICA SEEDS - M.I.J. UMBOH (BIOTROPIA, 1987)
Seeds  of  Shorea  javanica  K  &  V  (Dipterocarpaceae),  were  subjected  to  different  treatments  of temperature (27 ± 2°C, 20 ± 2°C and < 10°C), coating (ash and paraffin) and relative humidity (20, 66 and 86%) and their germination capability as well as moisture content assessed after 3, 7, 14 and 30 days of storage. The germination percentage of  the seeds stored 30 days  in a  cloth bag under different  conditions of temperature showed highly significant differences  (a = 0.01). No significant differences were  found on  the effect of coating, duration of storage as well as on the interaction between these two factors. The moisture content of the seeds between 13 and 14% gave a germination percentage above 50% after 30 days.